A Convenient One-Pot Synthesis of Both Enantiomers of 1,3,5-Trisubstituted Hydantoins - Han, Gun Hee; Kim, Seo Yun; Lee, Ha Rim; Lee, Ji Su; Park, Yong Sun (Synlett, 2020)
A novel one-pot asymmetric synthetic method for the direct conversion of bromoacetates into highly substituted hydantoins has been developed. Both enantiomers of 1,3,5-trisubstituted hydantoins were conveniently synthesized through a dynamic kinetic resolution of bromoacetates derived from either ethyl l-lactate or diacetone-d-glucose. The sequential three-component reaction permitted the preparation of (R)- or (S)-1,3,5-trisubstituted hydantoins in yields of 77–51% with enantiomeric ratios of up to 95:5.
Keywords: hydantoins; one-pot reaction; asymmetric synthesis; kinetic resolution; chiral auxiliaries; bromoacetates